Modelling the local geoid of East Kalimantan from combination of airborne and terrestrial gravity data using the KTH method - Oktavia, Sukma Nur; Heliani, Leni Sophia (Geodesy and Cartography, 2026)
This research aims to determine the gravimetric geoid using the KTH method for East Kalimantan, where Indonesia’s new capital city is located. The geoid of East Kalimantan was calculated from a combination of airborne gravity data, terrestrial gravity data, DTU17 for the sea area, anomalies of EGM2008 degree 2190, SRTM15+, and GGM from EGM2008 degree 360. The geoid modelling is performed using LSMSSOFT software with a grid interval of 0.01˚. The evaluation of capsize variations includes 14 variations: 0.1˚, 0.2˚, 0.3˚, 0.4˚, 0.5˚, 0.6˚, 0.7˚, 0.8˚, 0.9˚, 1˚, 1.2˚, 1.3˚, 1.5˚, and 2˚. The KTH geoid was evaluated using 264 GNSS-Levelling data points. The best accuracy was obtained at a capsize of 0.6˚ with a standard deviation value of 0.0532 m. The accuracy of the geoid model after shifting to the tidal benchmark (BM) is 0.0526 m. A comparison with the recent national geoid model of INAGEOID2020 v.2 obtained using the Remove-Restore method, which has a standard deviation of 0.0588 m, shows that the accuracy of the KTH method geoid model is higher, with a precision improvement of 0.0062 m.